(In)visibilities of the Body in the Circus: : mapping university extension initiatives in Brazilian universities - Fernandes, Rita de Cassia; da Nóbrega, Terezinha Petrucia (Revista Brasileira de Estudos da Presença, 2025)
The research analyzes the (in)visibilities, spaces and temporalities of the body in the circus in university extension initiatives of Brazilian Universities. The method is based on the description of experiences and phenomenological reduction, using images and focus group meetings. The research findings indicate the perception of the body in circus practices as an expressive and educational potential. In addition, they suggest that the Brazilian university extension needs more focus on the body in the circus, especially if we consider the growing demand for professionals and increased number of shows, circus schools, among others.